Supervision Content Needs Analysis for A Teacher Sustainability Professional Program - Rifma Rusli; Ranti Meizatri; Jasrial Jasrial; Rusdinal Rusdinal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The research aims at describing the teachers’ need to supervise content in their professional development. The research was conducted with a quantitative descriptive design whose respondents were elementary school teachers in four districts/cities in West Sumatra, namely: Padang Panjang, Payakumbuh, Padang, and Pesisir Selatan. The sample, 108 teachers consisting of 75 female and 33 male teachers, were selected by using a proportional random sampling technique. The data were collected by using an online questionnaire which was arranged based on two indicators of content supervision of teacher professional improvement, namely commitment and the ability to think abstractly. The result shows that there are 16 contents of supervision related to commitment and abstraction needed by teachers for competency improvement and professional development. Supervision of content that is relevant to the needs of teachers' fundamental competencies allows for an increase in the ability of teachers to respond well to various changes and challenges in carrying out their tasks. This research implies that this content supervision needs to be developed into more comprehensive theoretically and practically.